Protracted Transition. Management of residential built heritage in the historic center of Rostov-on-Don, Russia - Batunova Elena; Davletshina Albina; Neugebauer Carola (Lodz University of Technology Press, 2023)
In urban development, residential heritage is a space for the challenging process of demarcation and negotiation between public and private. The complexity increases when the relationship between the public and the individual changes dramatically, and the evolution of rules defining this relationship is not complete. Since the USSR collapsed, large Russian cities have transformed radically due to the privatization of land and real estate, commercialization of urban space, and the increasing role of non-state actors in urban development. At the same time, most of these processes are not finalized. There are ‘ownerless’ land plots, buildings, or infrastructures in a highly fragmented urban fabric and contradictions or gaps in the legal framework related to responsibilities, obligations, and rights in the field of urban development. Based on the case of the historic center of Rostov-on-Don in Russia, the paper examines how institutional transition influences the existing institutional approaches to residential heritage use, management, and preservation. Our findings demonstrated the transitional context largely determines the existing practices, and the local institutions cannot overcome the existing gaps and contradictions in legislation, property rights definition, and management.
Keywords: built heritage; urban fabric; institutional practices; post-socialist transition; dziedzictwo budowlane; tkanka miejska; praktyki instytucjonalne; transformacja postsocjalistyczna; Rosja; Russia